2022
DOI: 10.1186/s12985-021-01732-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of human papillomavirus genotypes among women attending gynecology clinics in northern Henan Province of China

Abstract: Background Human papillomavirus (HPV) infection can cause cervical and other cancers, including vulva, vagina, penis, anus, or oropharynx. However, in China's northern Henan Province, data on the prevalence and genotype distribution of HPV among women attending gynecology clinics is limited. This study aimed to investigate the current prevalence and genotype distribution of HPV among women attending gynecology clinics in northern Henan Province. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 34 publications
8
19
1
Order By: Relevance
“…We also presented age-specific prevalence of single, dual and multiple HPV infections. The single genotype infection in aged ≤ 24 years group was higher than that of dual and multiple infections in other age groups, which also observed in northern Henan province of China [ 37 ]. Young women are thought to have more frequent sexual activities, more than one partner and relatively inadequate immune response, which makes them have a higher probability of exposure to HPV infection.…”
Section: Discussionmentioning
confidence: 85%
“…We also presented age-specific prevalence of single, dual and multiple HPV infections. The single genotype infection in aged ≤ 24 years group was higher than that of dual and multiple infections in other age groups, which also observed in northern Henan province of China [ 37 ]. Young women are thought to have more frequent sexual activities, more than one partner and relatively inadequate immune response, which makes them have a higher probability of exposure to HPV infection.…”
Section: Discussionmentioning
confidence: 85%
“…This study was a large-scale HPV screening study among women in the region, and the results were closely related to the unique research population. Results showed that the overall HPV infection rate in the regular screening population was 9.6%, which was significantly lower than the HPV infection rate in women who visited the gynaecology department of hospitals [ 35 , 36 ]. Although the hospital (gynaecology) patients were a selected group and were therefore likely to have a higher overall rate of HPV positive testing, the trends with age were the same in both the general population and the hospital population [ 33 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, HPV infection is recognized as a major causative agent in the development of cervical cancer which remains the fourth most common cancer among women worldwide with an estimated 569,847 new cases and 311,365 deaths in developing countries in 2018 [ 4 6 ]. Currently, more than 150 HPV genotypes have been identified and about 40 are known to transmit through sexual contact and to infect the anogenital region [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%